Analisis Faktor Yang Memengaruhi Kepuasan Kerja Tenaga Medis Di RSU Sinar Husni Deli Serdang - Hepi Irawan; Juliandi Harahap; Ramadhani Syafitri Nasution (Pusat Riset dan Inovasi Nasional, 2024)
Human resources are a very important factor in an organization. Medical personnel are human resources to achieve hospital goals. In order for hospital goals to be achieved effectively and efficiently, management is required to be able to provide job satisfaction to its medical personnel. The aim of the research is to determine and analyze the factors that influence the job satisfaction of medical personnel at RSU Sinar Husni Deli Serdang in 2023. The research design used in this research is an analytical survey with a cross sectional design. The population in this study was all medical personnel at RSU Sinar Husni Deli Serdang, totaling 138 people, the number of samples to be studied was 102 people, the sampling technique used was purposive sampling, data analysis was carried out using univariate, bivariate and multivariate analysis. . The statistical tests used are the chi square test and logistic regression. The results of the chi square test research show that the independent variables, namely salary p= 0.001, coworkers p= 0.001, supervision p= 0.002, promotion p= 0.003 and job characteristics p= 0.008 have a p-value of 0.001 < α 0.05, meaning salary , colleagues, supervision, promotions and job characteristics influence job satisfaction of medical personnel at RSU Sinar Husni Deli Serdang and the results of the multiple logistic regression test show that the salary variable has an odds ratio (OR) of 3.188. The conclusion is that salary, co-workers, supervision, promotion and job characteristics influence medical personnel at RSU Sinar Husni Deli Serdang. It is recommended that efforts that need to be made by hospital management are to increase the provision of incentives and rewards for those who are better so that they can motivate them to provide maximum service to patients.